Crimes of the powerful : a reader a reader - Whyte, David, 1968- (Maidenhead, Berkshire, England : Open University Press McGraw-Hill Education, 2009)
"Crimes of the powerful - the crimes committed by state institutions and private business organizations or corporations - are often overlooked by Criminology, or are treated at best as a mildly interesting diversion from the real business of crime and criminal justice. Indeed, academic Criminology in the main tends to reinforce the idea that the real problems of society can be located in the lower strata of society and is yet to come to terms with overwhelming evidence that crimes of the institutionally powerful kill, rip off and steal from more people than crimes committed by individuals. This ... Reader introduces debates on crimes of the powerful with a selection of 45 extracts from key authors. The book is organised into the following sections: State, Violence and Crime; Partners in Crime; Capitalism and Crimes of the Powerful; Law and the Corporation; Explanations; Definitions; The Problem of Criminalization."--Back cover.
Includes bibliographical references and index.
Keywords: Commercial crimes; Corporations -- Corrupt practices; Organized crime; Political corruption; White collar crimes; Power (Social sciences); Elite (Social sciences); Commercial crimes; Corporations -- Corrupt practices; Elite (Social sciences); Organized crime; Political corruption; Power (Social sciences); White collar crimes